Peran Inklusi Keuangan dalam Memediasi Pengaruh Financial Technology dan Literasi Keuangan terhadap Kinerja UMKM di Kota Semarang - Astohar Astohar; Mirna Dyah Praptitorini; Maulana Ihsan Yusufi Suyatno; Jumlatul Aulia (Jurnal Akuntan Publik, 2024)
Micro, Small and Medium Enterprises (MSMEs) are the supporting sector of the country's economy and are able to survive in any conditions, including when the economic crisis hits. MSME business development is very necessary so that performance can always be improved and business continuity can be maintained. The results of a preliminary survey on MSMEs in Semarang City show that the average financial performance of MSMEs is still fluctuating (up and down). Based on phenomena and research gaps (developing) research by adding financial literacy variables. The object of this research was carried out on MSMEs in Semarang City with a final sample size of 144 using the cluster random sampling method (per sub-district). The analysis tool uses a regression equation test with a mediation test using the Sobel test. The research results show that the variables fintech, financial literacy, financial inclusion of MSMEs and MSME performance in Semarang City have sufficient values ​​in the interval 2.33 to 3.65, with MSME performance with the highest average. The fintech and financial literacy variables have been proven to have a positive and significant effect on the financial inclusion of MSMEs in Semarang City. Fintech, financial literacy and financial inclusion of MSMEs have proven to influence the performance of MSMEs in Semarang City. MSME financial inclusion has been proven to mediate the influence of financial literacy on MSME performance in Semarang City, however, financial inclusion has not been proven to mediate the influence of fintech on MSME performance.